2008
DOI: 10.1161/circresaha.108.186015
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase Expression and Cardiomyocyte Dysfunction During Sustained Moderate Ischemia in Pigs

Abstract: Abstract-In acute myocardial ischemia, regional blood flow and function are proportionally reduced. With prolongation of ischemia, function further declines at unchanged blood flow. We studied the involvement of an inflammatory signal cascade in such progressive dysfunction and whether dysfunction is intrinsic to cardiomyocytes. In 10 pigs, ischemia was induced by adjusting inflow into the cannulated left anterior coronary artery to reduce coronary arterial pressure to 45 mm Hg (ISCH); 4 pigs received the indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 65 publications
1
28
0
Order By: Relevance
“…This may be explained by an undiscovered endothelial mediator(s) that improved myocardial microcirculation in the group P. in group P. v. Reperfusion injury syndrome to be deleted, interestingly the study results showed that immediate myocardial reperfusion might be unnecessary. The procedure, provides stabilization as well as myocardial and hemodynamic recoveries without the urgent need of reperfusion with the well known consequences of the reperfusion injury syndrome (Heinzel, et al, 2008). This was confirmed with our ongoing study, using an intrapulmonary catheter device induced percutaneously through the jugular vein.…”
Section: Commentsupporting
confidence: 75%
“…This may be explained by an undiscovered endothelial mediator(s) that improved myocardial microcirculation in the group P. in group P. v. Reperfusion injury syndrome to be deleted, interestingly the study results showed that immediate myocardial reperfusion might be unnecessary. The procedure, provides stabilization as well as myocardial and hemodynamic recoveries without the urgent need of reperfusion with the well known consequences of the reperfusion injury syndrome (Heinzel, et al, 2008). This was confirmed with our ongoing study, using an intrapulmonary catheter device induced percutaneously through the jugular vein.…”
Section: Commentsupporting
confidence: 75%
“…For example, compared with normal controls, left ventricular biopsy samples from explanted failing human hearts express elevated levels of S-nitrosylated tropomyosin (18). Although the effect of tropomyosin S-nitrosylation on actomyosin ATPase function has not been fully characterized, these observational data raise speculation that S-nitrosylation of tropomyosin may modulate the adverse downstream actions of iNOS-derived NO on myocyte contractility that has been observed previously in certain animal models of coronary ischemia (57).…”
Section: S-nitrosylation In Cardiovascular Diseasesmentioning
confidence: 85%
“…10 With increasing duration of ischemia, perfusion-contraction matching is progressively lost. 9,11 The pathophysiological concept of perfusion-contraction matching coincided with the clinical observation of hibernating myocardium by Shahbudin Rahimtoola, 12 and the idea emerged that indeed perfusion-contraction matching permits adaptation of the myocardium to ischemia and, in consequence, maintenance of its viability and eventual recovery after revascularization. 13 Indeed, perfusion-contraction matching is a hallmark of hibernation.…”
Section: T His Pioneering Article Was the First To Quantitatively Relmentioning
confidence: 90%